2019
DOI: 10.37190/epe190307
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of the concentrations and mass size distributions of particulate matter in indoor sports facilities before and during athlete training

Abstract: The mass size distribution of five fractions of particulate matter inside most popular types of closed sports facilities before and after athlete training were compared. In all the facilities, the concentrations of particles were higher during the training than before it. Their values depended on the type of flooring and cubic capacity of the rooms. Particle mass size distribution importantly affects the particle deposition rate in the respiratory tract. The results of the work indicate the necessity of furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…It is well documented that exposure to high PM on a short-term scale ( Levy, Hammitt & Spengler, 2000 ; Nawrot et al, 2011 ; Provost et al, 2016 ) and in the long term ( Beelen et al, 2014 ) increases the risk of many serious diseases, including cardiovascular and respiratory diseases ( Du et al, 2016 ; Jo et al, 2017 ) especially in children ( Saenen et al, 2016 ) and the elderly ( Halonen et al, 2009 ; Simoni et al, 2015 ). A topic which has now been receiving special attention is the impact of air pollution on the health of physically active people ( An et al, 2017 ; Giles & Koehle, 2013 ) practicing sports in the open air, including athletes ( Kuskowska, Rogula-Kozłowska & Widziewicz, 2019 ; Reche et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that exposure to high PM on a short-term scale ( Levy, Hammitt & Spengler, 2000 ; Nawrot et al, 2011 ; Provost et al, 2016 ) and in the long term ( Beelen et al, 2014 ) increases the risk of many serious diseases, including cardiovascular and respiratory diseases ( Du et al, 2016 ; Jo et al, 2017 ) especially in children ( Saenen et al, 2016 ) and the elderly ( Halonen et al, 2009 ; Simoni et al, 2015 ). A topic which has now been receiving special attention is the impact of air pollution on the health of physically active people ( An et al, 2017 ; Giles & Koehle, 2013 ) practicing sports in the open air, including athletes ( Kuskowska, Rogula-Kozłowska & Widziewicz, 2019 ; Reche et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to Newman’s research, saline inhalations with the use of nebulisers result in the deposition of 10–40% of the inhaled substance (physiological saline solution of 0.9% NaCl) in the lungs, and the effectiveness of inhalation depends, among others, on skills, mask tightness and equipment efficiency [ 64 , 65 ]. The literature review proves that the studies described in this publication are one of the first studies on PM deposition in the respiratory tract of people receiving therapy in mine chambers, therefore the authors compared the obtained results to the results of studies carried out in indoor sports rooms, where a similar deposition model was used [ 66 ]. Comparing the results of these two studies, it can be concluded that the DF in the mine is higher than the DF calculated for indoor sports rooms, where for people at rest they take values in the range 0.32–0.35, and 0.50–0.65 for exercising people, assuming twice the frequency and depth of breathing caused by physical activity [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The literature review proves that the studies described in this publication are one of the first studies on PM deposition in the respiratory tract of people receiving therapy in mine chambers, therefore the authors compared the obtained results to the results of studies carried out in indoor sports rooms, where a similar deposition model was used [ 66 ]. Comparing the results of these two studies, it can be concluded that the DF in the mine is higher than the DF calculated for indoor sports rooms, where for people at rest they take values in the range 0.32–0.35, and 0.50–0.65 for exercising people, assuming twice the frequency and depth of breathing caused by physical activity [ 66 ]. Relatively high DFs in the mine result from the high percentage of fine particles in the PM mass.…”
Section: Resultsmentioning
confidence: 99%
“…The chamber was ventilated using a powered ventilation system. While the ELPI sampling was stopped, particle concentration in the chamber was monitored using DustTrak 8534 DRX Aerosol Monitor sampler (TSI, MN, USA), which was calibrated using a previously reported procedure [ 59 ]. The ventilation continued until the concentration of particles with diameters less than 10 µm, as measured using DustTrak 8534 DRX (TSI, MN, USA), was less than 10 4 m −3 .…”
Section: Methodsmentioning
confidence: 99%